An updated systemic review and meta-analysis on human papillomavirus in breast carcinogenesis - Awan, Usman Ayub; Khattak, Aamer Ali; Ahmed, Noman; Guo, Xingyi; Akhtar, Sohail; Kamran, Shehrish; Yongjing, Zhao; Liu, Jianbo; Khan, Suliman (Frontiers in Oncology, 2023)
Background: Breast Cancer (BC) stands out as the widely prevalent malignancy among all the types of cancer affecting women worldwide. There is significant evidence that the pathogenicity of BC may be altered by Human Papillomavirus (HPV) infection; however, conclusive data are not yet available. Methods: By searching five databases, including EMBASE, IBECS, PubMed, Scopus, Science Direct, Google Scholar, and Web of Science, a thorough systematic analysis was conducted on the prevalence of HPV in BC patients from 1990 to June 30, 2022. After applying extensive eligibility criteria, we selected 74 publications for further analysis based on the prevalence of HPV infections in breast tissues. All of the data were analyzed using a random-effects meta-analysis, Cochran Q test and I2 statistic were used to calculate the heterogeneity of the prevalence among these studies using subgroup analysis. Variations in the HPV prevalence estimates in different subgroups were evaluated by subgroup meta-analysis. Results: In total, 3156 studies were initially screened, resulting in 93 full-text studies reviewed, with 74 meeting inclusion criteria. Among a total of 7156 BC biopsies, the pool prevalence of HPV was 25.6% (95% CI= 0.24-0.33, τ2=0.0369 with significant heterogeneity between estimates (I2 = 97% and p < 0.01). Consequently, 45 studies with available controls were further studied, and the prevalence of HPV in case-control studies was 26.2% with overall odds 5.55 (95% CI= 3.67-8.41, I2=38%, τ2=1.4878, p < 0.01). Further subgroup analysis of HPV revealed HPV-16 had a maximum prevalence of 9.6% (95% CI= 3.06-11.86, I2=0%, τ2=0.6111, p < 0.01). Among different geographical regions, Europe reported the maximum prevalence of HPV, i.e., 39.2% (95% CI=1.29-7.91, I2=18%, τ2=1.2911, p < 0.01). Overall distribution showed HPV-18 was a frequent HPV subtype reported in Australia. Conclusion: Current study provides a global estimate of HPV prevalence in BC patients and demonstrates a significant association between this virus and BC etiology. Nevertheless, we recommend further investigation into the underlying mechanism is essential to validate this hypothesis.